The Urgency of Spirituality as an Effort to Prevent Violence in Guidance and Counseling - Zulkarnain, Ahmad; Wati, Ina Ambar (Psikopedagogia, 2019)
The study aims to determine the importance of spirituality in guidance and counseling. It’s a qualitative study with a descriptive narrative type. This study integrates a literature review with data obtained through interview techniques. The snowball sampling technique determined the subjects in the study. The study results were analyzed using a descriptive narrative approach. The results of the study show that counselors who have internalized spiritual values will make mutual respect, maintain mutual harmony, and work without violence as the basis for carrying out their duties as a helper, both on campus, at school, and other educational institutions. The results of the study can be used as a reference that the counselor should always develop spiritual values so that he can avoid acts of violence when providing services.